CLUSTER MECHANISM OF SOLID PHASE FORMING AT THE EXAMPLE OF GROWTH OF ALUMINIUM SINGLE-CRYSTALS OF MELT - V. B. Vorontsov; D. V. Zhuravlev (Литьë и металлургия)
The interrelation between frequencies of acoustic emission signals during crystallization of aluminium and kinetics of surface movement is established.